2016
DOI: 10.1089/acm.2015.0257
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Enhancing Herbal Formulae in Korean Medicine: Identification of Candidates by Text Mining and Literature Review

Abstract: Twenty-three candidates were selected for cognitive-enhancing herbal formulae and their main constituents. For 14 herbal formulae among the 23 candidates, on average 5.6 published research papers per herbal formula describing cognitive-enhancing effects were found. In addition, some published papers were identified for 5 main constituents most frequently used to make up the 23 candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Step 2—Intervention selection: The most common method used to inform selection of interventions involved positioning the traditional evidence alongside scientific evidence, contemporary texts and/or expert opinion to draw comparisons, validate evidence or develop a ‘totality of evidence’ (Adams et al, 2007, 2011; Adams, Schneider, et al, 2012; Arabshahi et al, 2015; Bae et al, 2019; Buentzel et al, 2020; Chen et al, 2015; Choi et al, 2015; De Vos, 2010; Fatali, Emami, et al, 2020; Fatali, Sadeghpour, et al, 2020; Guo‐Jing et al, 2020; Han et al, 2017; Lardos et al, 2011; Leach et al, 2018; May et al, 2016; Pae et al, 2016; Park et al, 2018; Petran et al, 2020; Sahranavard et al, 2014; Steel & Adams, 2011b; Thomas, 2011; Watkins et al, 2012; Xia et al, 2020; Yang et al, 2019; Zhang et al, 2014). It was also common for selection processes to place importance on TK with greater predominance in traditional sources, such as interventions appearing frequently within or across sources, and those with consistency of use over time as proxy measures for safety and potential efficacy (Alizadeh et al, 2017; Bae et al, 2019; Birch & Sherman, 1999; Buentzel et al, 2020; Chen et al, 2015, 2020; Connelly et al, 2020; De Vos, 2010; Flatt, 2016; Guo‐Jing et al, 2020; Han et al, 2017; Lardos et al, 2011; May et al, 2014; Sahranavard et al, 2014; Steel & Adams, 2011c; Thomas, 2011; Xia et al, 2020; Zhang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Step 2—Intervention selection: The most common method used to inform selection of interventions involved positioning the traditional evidence alongside scientific evidence, contemporary texts and/or expert opinion to draw comparisons, validate evidence or develop a ‘totality of evidence’ (Adams et al, 2007, 2011; Adams, Schneider, et al, 2012; Arabshahi et al, 2015; Bae et al, 2019; Buentzel et al, 2020; Chen et al, 2015; Choi et al, 2015; De Vos, 2010; Fatali, Emami, et al, 2020; Fatali, Sadeghpour, et al, 2020; Guo‐Jing et al, 2020; Han et al, 2017; Lardos et al, 2011; Leach et al, 2018; May et al, 2016; Pae et al, 2016; Park et al, 2018; Petran et al, 2020; Sahranavard et al, 2014; Steel & Adams, 2011b; Thomas, 2011; Watkins et al, 2012; Xia et al, 2020; Yang et al, 2019; Zhang et al, 2014). It was also common for selection processes to place importance on TK with greater predominance in traditional sources, such as interventions appearing frequently within or across sources, and those with consistency of use over time as proxy measures for safety and potential efficacy (Alizadeh et al, 2017; Bae et al, 2019; Birch & Sherman, 1999; Buentzel et al, 2020; Chen et al, 2015, 2020; Connelly et al, 2020; De Vos, 2010; Flatt, 2016; Guo‐Jing et al, 2020; Han et al, 2017; Lardos et al, 2011; May et al, 2014; Sahranavard et al, 2014; Steel & Adams, 2011c; Thomas, 2011; Xia et al, 2020; Zhang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“… 12 Additionally, 14 of 23 herbs that enhance cognition have been evaluated experimentally and clinically. 9. , 10 In the current study, we found 52 skincare herbs and reviewed the modern literature for reports regarding these herbs.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Recently, computer-aided approaches have been used to study Korean traditional medicine. 8 The analysis of Donguibogam terms led to the discovery of novel candidate cognition-enhancing herbs, 9. , 10 candidate anti-aging herbs, 11 stroke treatments, 12 and prescriptions for Parkinson-type rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…These theories render the proposed approach useful in identifying novel relationships between diseases and drugs that have a high probability of being physiologically effective. On the other hand, existing TCM drug mining primarily focuses on the assessment of ancient classic literature, with less analysis of herbal components (May et al, 2014 ; Pae et al, 2016 ), and thus may affect knowledge dissemination. Our study is the first to combine well-known TCM database with text mining approaches.…”
Section: Discussionmentioning
confidence: 99%